8
$\begingroup$

This is an interesting question I came across, and it does not look that easy:

$365$ can be written as a sum of $2$ consecutive squares and also $3$ consecutive squares:

$$ \large 365 = 14^2 + 13^2 = 12^2 + 11^2 + 10^2$$

What is the next number with this property? Give the last $3$ digits of the number.

The squares cannot be zero.

(I have no idea what is the deal with "last $3$ digits" part, but this is the original form of the problem)

$\endgroup$
  • 1
    $\begingroup$ This boils down to integer roots of the polynomial $$p(k,n) = k^2 + (k+1)^2 - n^2 - (n+1)^2 - (n+2)^2$$ $\endgroup$ – AlexR Sep 30 '14 at 7:07
  • 1
    $\begingroup$ As Yves has hinted, this does not contain a worked solution, just an answer: The next number is $35645 = 133^2 + 134^2 = 108^2 + 109^2 + 110^2$, and in fact the increasing sequence $(a_n)$ of all such numbers satisfies the Lucas-like recurrence relation $a_n=99(a_{n−1}−a_{n−2})+a_{n−3}$. The sequence is given at oeis.org/A007667 $\endgroup$ – Travis Sep 30 '14 at 7:21
  • 1
    $\begingroup$ Thanks, I am flabbergasted to see 99 in the recurrence formula! :) Why 99? $\endgroup$ – VividD Sep 30 '14 at 7:25
  • 1
    $\begingroup$ @Travis: Note that, $$1^5+2^5+\dots+\color{brown}{13}^5 = 1001^2$$ $$1^5+2^5+\dots+\color{brown}{133}^5 = 971299^2$$ and which is not coincidence. Kindly see my answer. $\endgroup$ – Tito Piezas III Jan 12 '16 at 15:09
  • 1
    $\begingroup$ @VividD: I hope you enjoy the surprises below. :) $\endgroup$ – Tito Piezas III Jan 12 '16 at 16:05
10
$\begingroup$

The problem reduces to, $$k^2+(k+1)^2=(n-1)^2+n^2+(n+1)^2\tag1$$

or simply,

$$2k^2+2k-1 = 3n^2\tag2$$

Making a quadratic into a square is a well-studied subject. The complete solution is given by,

$$k = \frac{3p^2\pm6pq+4q^2}{3p^2-2q^2}$$

where $3p^2-2q^2=1$. We can transform this condition into a more conventional Pell equation by using the substitutions (the trick is described in this post),

$$p,\,q = u^2+4uv+6v^2,\quad u^2+6uv+6v^2$$

and $u,\pm v$ solve,

$$u^2-6v^2=1$$

Example.

Substitute $\displaystyle k = \frac{3p^2\pm6pq+4q^2}{3p^2-2q^2}$ into the LHS of $(1)$ and we get,

$$F_{\pm}(u,v):= k^2+(k+1)^2 = \frac{45 p^4 \pm 108 p^3 q + 120 p^2 q^2 \pm 72 p q^3 + 20 q^4}{(3p^2-2q^2)^2}$$

bearing in mind that $p,\,q = u^2+4uv+6v^2,\; u^2+6uv+6v^2$ and $u^2-6v^2=1$. Thus,

$$F_-(1,0) = 5$$ $$F_+(1,0) = 365$$ $$F_+(5,-2) = 35645$$ $$F_-(5,-2) = 3492725$$ $$F_-(5,2) = 342251285$$ $$F_+(5,2) = 33537133085$$

which are indeed the first few terms of the sequence A007667.

First surprise.

The $k$ are,

$$k =1, 13, 133, 1321, 13081, 129493,\dots$$

which is sequence A031138 and also defined as,

$$1^5+2^5+3^5+\dots+k^5 = y^2$$

Example:

$$1^5+2^5+3^5+\dots+13^5 = 1001^2$$

Second surprise.

The $n$ are,

$$n = 1, 11, 109, 1079, 10681, 105731,\dots$$

which is A054320 though more interestingly (as A253475),

$$x=\frac{n+1}{2} = 1, 6, 55, 540, 5341, 52866, 523315,\dots$$

with a complementary sequence A054318,

$$y = 1, 5, 45, 441, 4361, 43165, 427285,\dots$$

then,

$$x^2 + (-x + 1)^2 = y^3 + (-y + 1)^3$$

$$4x(x\pm1)+1 = \text{square}$$

$$6y(y-1)+1 = \text{square}$$

Thus, the rather simple original equation turns out to involve relations between second, third, and fifth powers.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.